Detection of Malignant Middle Sacral Vein Tumor Thrombus in a Recurrent Rectal Cancer Case Using 18F-FDG PET/CT (Bangladesh Journal of Nuclear Medicine, 2026)
Tumor thrombus represents an uncommon but clinically significant manifestation of malignancy, most frequently associated with renal cell carcinoma and hepatocellular carcinoma. In colorectal cancer, venous tumor thrombus is exceedingly rare and often underrecognized, with potential implications for staging, prognosis, and therapeutic planning. In this report, a case of carcinoma rectum is presented with FDG-avid tumor thrombus, highlighting the diagnostic utility of PET/CT in this unusual clinical scenario. This case demonstrates the distinct diagnostic advantage of 18F FDG PET/CT, where its high sensitivity for metabolic activity uniquely differentiates malignant tumor thrombus from bland post-radiation fibrosis or lymph node—a critical distinction that anatomical imaging alone frequently fails to achieve.Bangladesh J. Nuclear Med. 29(1): 92-95, 2026